2022
DOI: 10.3390/plants11192623
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and Therapeutic Potential of Kaempferol and Quercetin: New Insights for Plant and Human Health

Abstract: Plant secondary metabolites, especially flavonoids, are major metabolites widely found in plants that play several key roles in plant defence and signalling in response to stress conditions. The most studied among these flavonoids are kaempferol and quercetin due to their anti-oxidative potential and their key roles in the defence system, making them more critical for plant adaptation in stress environments. Kaempferol and quercetin in plants have great therapeutic potential for human health. Despite being wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(38 citation statements)
references
References 135 publications
0
38
0
Order By: Relevance
“…In terms of flavonoids, they have been widely reported for their contribution in plant biotic and abiotic stress response ( Jan et al, 2022 ). Our results found that quercetin, rutin and galangin were up regulated in the resistant genotype infected with U. appendiculatus at both time points.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of flavonoids, they have been widely reported for their contribution in plant biotic and abiotic stress response ( Jan et al, 2022 ). Our results found that quercetin, rutin and galangin were up regulated in the resistant genotype infected with U. appendiculatus at both time points.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids in food, like quercetin and myricetin, protect against oxidative stress and aging [ 43 ]. The flavonoids under investigation in our study are considered dietary flavonoids and have many health benefits, including their use as supplements [ 43 , 44 , 45 ]. Similarly, phenolic acids are also considered important dietary components of the human diet [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that kaempferol, as a precursor of ubiquitin-ketone (coenzyme Q) biosynthesis, is an atypical node between primary and specialized metabolism (Soubeyrand et al, 2018;Berger et al, 2022). Kaempferol is involved in plant defense and signaling in response to stressful conditions (Soubeyrand et al, 2018;Jan et al, 2022). Dihydrokaempferol is involved in plant growth and development.…”
Section: Morphological Characteristics Of Litchi Seedsmentioning
confidence: 99%